The Perception of Civil Servants Regarding the Equalization of Structural Positions into Functional Positions and Its Influence on Work Productivity at Ganesha Education University - Santhi, Ketut Susila; Komang Krisna Heryanda; Kadek Rai Suwena (Universitas Sains dan Teknologi Komputer, 2024)
The purpose of this study was to determine the perceptions of civil servants regarding the equalisation of structural positions into functional positions and their influence on work productivity at Ganesha University of Education. This research uses quantitative descriptive method. The sampling technique used was purposive sampling with a sample size of 59 employees who have the position of head of section and subsection. Collection using interview techniques and questionnaires. Data analysis using a mixed method approach through qualitative descriptive analysis and quantitative analysis using paired sample t-test. The results showed that (a) the implementation of equalisation of structural positions into functional positions at Ganesha University of Education is a bureaucratic reform in accordance with Permenpan-RB Number 17 of 2021 concerning Equalisation of Administrative Positions into Functional Positions; (b) the perception of civil servants towards the transfer of positions shows that the implementation of the transfer of positions has not optimally increased work productivity due to the determination of functional positions that are limited in number and type so that they do not match employee competence; (c) the results of the paired sample T-test test on there are differences in the work productivity of civil servants at Ganesha University of Education before and after equalisation of structural positions into functional positions